Infrared thermography and calibration techniques for gas turbine applications: a review - Falsetti, C; Sisti, M; Beard, PF (Elsevier, 2020)
This paper presents a comprehensive review of the calibration techniques for infrared (IR) measurements in the field of gas turbines. When performing IR thermography in challenging environments, such those of gas turbine experiments, particular attention must be paid to (i) the target emissivity, function of temperature, surface conditions and observation angle, (ii) the surroundings reflected radiation and (iii) the optical pathway transmittance.